One-Step Cohydrothermal Synthesis of Nitrogen-Doped Titanium Oxide Nanotubes with Enhanced Visible Light Photocatalytic Activity - Cheng-Ching Hu; Tzu-Chien Hsu; Li-Heng Kao (International Journal of Photoenergy)
Nitrogen-doped TiO2 nanotubes with enhanced visible light photocatalytic activity have been synthesized using commercial titania P25 as raw material by a facile P25/urea cohydrothermal method. Morphological and microstructural characteristics were conducted by transmission electron microscopy, powder X-ray diffraction, and nitrogen adsorption/desorption isotherms; chemical identifications were performed using X-ray photoelectron spectroscopy, and the interstitial nitrogen linkage to the TiO2 nanotubes is identified. The photocatalytic activity of nitrogen-doped TiO2 nanotubes, evaluated by the decomposition of rhodamine B dye solution under visible light using UV-vis absorption spectroscopy, is found to exhibit ~ four times higher than that of P25 and undoped titanate nanotubes. Factors affecting the photocatalytic activity are analyzed; it is found that the nitrogen content and surface area, rather than the crystallinity, are more crucial in affecting the photocatalytic efficiency of the nitrogen-doped TiO2 nanotubes.